Development Finance via Diaspora Bonds: Track Record and Potential - Ketkar, Suhas L.; Ratha, Dilip (World Bank, Washington, D.C., 2013)
A diaspora bond is a debt instrument issued by a country - or potentially, a sub-sovereign entity or a private corporation - to raise financing from its overseas diaspora. Israel and India have raised $35-40 billion using these bonds. Drawing on their experiences, this paper discusses the rationale, methodology, and factors affecting the issuance of diaspora bonds for raising external development finance. The Government of Israel has offered a flexible menu of diaspora bonds since 1951 to keep the Jewish diaspora engaged. The Indian authorities, in contrast, have used this instrument for balance of payments support, to raise financing during times when they had difficulty in accessing international capital markets. Diaspora bonds are often sold at a premium to the diaspora members, thus fetching a "patriotic" discount in borrowing costs. Besides patriotism or the desire to do good in the investor's country of origin, such a discount can also be explained by the fact that diaspora investors may be more willing and able to take on sovereign risks of default in hard currency as well as devaluation as they may have local currency liabilities and they may be able to influence the borrower's decision to service such debt. The paper discusses several conditions for successful diaspora bond issuance having a sizeable diaspora, especially first-generation migrants, is understandably an important factor affecting the issuance of diaspora bonds. Countries with strong and transparent legal systems for contract enforcement are likely to find it easier to issue such bonds. Absence of civil strife is a plus. While not a pre-requisite, presence of national banks and other institutions in destination countries facilitates the marketing of bonds to the diaspora.